ICA II Alleviates Testicular Torsion Injury by Dampening the Oxidative and Inflammatory Stress - Chi, Ani; Yang, Bicheng; Cao, Xiaohui; Wang, Zhenqing; Liu, Hanchao; Dai, Hao; Deng, Chunhua; Zhang, Min (Frontiers in Endocrinology, 2022)
Testicular torsion-detorsion is an ischaemia-reperfusion-induced male gonad injury that may lead to male infertility. Oxidative stress plays an important role in the ischaemia-reperfusion injury. Icariside II (ICA II) prevents oxidative stress and has obvious protective effects on spermatogenic function. The present study was aimed to investigate therapeutic potentials of ICA II on testicular torsion. 72 mice were randomly divided into three groups: sham-operated control group (n = 24), testicular ischemia-reperfusion + saline group (n = 24) and testicular ischemia-reperfusion + icariside II treated group (n = 24). Testicular ischemia-reperfusion was induced by the left testis rotated 360 degrees in a clockwise direction for 30 minutes followed by detorsion, the contralateral testis was removed. ICA II in saline (5 mg/kg/day) was administrated by gavage immediately after detorsion. The results demonstrated that ICA II alleviated testicular damage by mitigating spermatogenic cell injury and improving testosterone production in mouse models of testicular torsion. We revealed that ICA II alleviated oxidative stress and apoptosis in the testes, reduced inflammatory infiltration and accelerated angiogenesis. Briefly, ICA II administration ameliorated testicular damage by improving spermatogenic function and testosterone production, which supports its use as a pharmacological treatment of testicular torsion.